2017
DOI: 10.1109/tifs.2017.2707332
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Signature Verification Method Based on an Interval Symbolic Representation and a Fuzzy Similarity Measure

Abstract: In this paper an efficient off-line signature verification method based on an interval symbolic representation and a fuzzy similarity measure is proposed. In the feature extraction step, a set of Local Binary Pattern (LBP) based features is computed from both the signature image and its under-sampled bitmap. Interval-valued symbolic data is then created for each feature in every signature class. As a result, a signature model composed of a set of interval values (corresponding to the number of features) is obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 51 publications
(123 reference statements)
0
23
0
Order By: Relevance
“…For this purpose, two different types of noise, namely Salt & Pepper, and Gaussian white noise were employed on the CEDAR dataset with various noise levels. It has been reported that these two types of noise commonly appear in images during the data collection process [53]. Thus, we added noise in the original signature images as follows: a) Salt and Pepper with parameters d=0.001, 0.01 and 0.1 and b) Gaussian with mean and variance parameters i) m=0 & v=0.01, ii) m=0 & v=0.1 and iii) m=0.2 & v=0.01.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, two different types of noise, namely Salt & Pepper, and Gaussian white noise were employed on the CEDAR dataset with various noise levels. It has been reported that these two types of noise commonly appear in images during the data collection process [53]. Thus, we added noise in the original signature images as follows: a) Salt and Pepper with parameters d=0.001, 0.01 and 0.1 and b) Gaussian with mean and variance parameters i) m=0 & v=0.01, ii) m=0 & v=0.1 and iii) m=0.2 & v=0.01.…”
Section: Resultsmentioning
confidence: 99%
“…The classification was carried out through an NN technique for Hindi and Bengali signatures separately. By using the same 117:15 dataset, promising results were found in [7] using a symbolic interval representation of signatures and fuzzy similarities. In this case, the authors performed experiments without separating Bengali and Hindi signatures.…”
Section: Signature Verification In Indic Languagesmentioning
confidence: 99%
“…Number of strokes/lognormals [83,248], * mathematical transformations (Wavelet [98,200,202,203], * Radon [268], * fractal [84], ** or others like total number, mean, and maximum of intra-/interstroke intersections, the number of x-axes, zero-crossings and the signature length [81,91,93,154,202,246,250]*), symbolic representation [7], * code vectors [234], * Sigma-lognormal based [83,102], * ...…”
Section: -Global Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…These features range from simple descriptors such as the size of the signature and inclination [16], graphometric features [17], [18], texture-based [19,20], interest point-based [21], among others. Recent advancements in this field include using multiple classifiers trained with different representations [20], using interval symbolic representations [22] and augmenting datasets by duplicating existing signatures or creating synthetic ones [23][24][25]. More recently, methods for learning features from signature images have been proposed [5][6][7][8].…”
Section: Related Workmentioning
confidence: 99%